The Western Flyer Crew - Monterey Peninusla Herald:::Creator::::::::::::
Monterey Peninsula Herald photo of The Western Flyer crew and passengers before leaving on the Sea of Cortez expedition. Left to right: Horace 'Sparky' Enea, Travis 'Tex' Hall, Rose 'Tootsie' Berry, Anthony 'Tony' Berry, Carol Steinbeck, John Steinbeck, and Ritzi 'Tiny' Colletto. Negative only!